(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The author in this article pays attention to the issue of protecting the national security of the Republic of Uzbekistan in the information sphere. As a result of the conducted research, the main elements of the Information Security Concept of the Republic of Uzbekistan are identified and formulated.